Declining propensity to pay? A re-examination of the lifecycle theory - Banyi, Monica L.; Kahle, Kathleen M. (Journal of Corporate Finance, 2014)
Our results indicate that the declining propensity to pay is a function of the changing composition of firms over time and not a declining propensity in individual firms themselves. In particular, the propensity to pay is greater than expected following the 2003 dividend tax cut. The decade a firm went public is also a major determinant of its initial payout policy. Finally, while the strength of the relation between earned/contributed capital and payout propensity declines across IPO decades, there is still a lifecycle effect — within a given IPO cohort, the likelihood of payout increases as firms age.